Analysis of Islamic Religious Education Learning Policy During the Pandemic: Opportunities and Challenge - Yanti Yanti; Aida Hayani; Farida Musyrifah; Nur Aeni Angger Rifqi Azieda (IJCAR: Indonesian Journal of Classroom Action Research, 2026)
This study aims to determine the impact of the distance learning policy during the pandemic on Islamic religious education teaching, as well as the opportunities and challenges faced by Islamic religious education lecturers at Alma Ata University. The study uses weekly evaluations of online learning sessions. The impact of the distance learning policy led lecturers to better understand and master technology for online media in each lesson, recognize the obstacles faced by students in online learning, and provide solutions for them. Alma Ata University has implemented e-learning for students, which can be accessed through the web using the internet. The results of this study show that in order to implement distance learning effectively, lecturers must be responsive and innovative to ensure that the teaching process runs smoothly.